A systematic mixed studies review on Organizational Participatory Research: towards operational guidance - Paula Louise Bush; Pierre Pluye; Christine Loignon; Vera Granikov; Michael T. Wright; Carol Repchinsky; Jeannie Haggerty; Gillian Bartlett; Sharon Parry; Jean-François Pelletier; Ann C. Macaulay (BMC Health Services Research, 2018)
Abstract Background Organizational Participatory Research (OPR) seeks organizational learning and/or practice improvement. Previous systematic literature reviews described some OPR processes and outcomes, but the link between these processes and outcomes is unknown. We sought to identify and sequence the key processes of OPR taking place with and within healthcare organizations and the main outcomes to which they contribute, and to define ideal-types of OPR. Methods This article reports a participatory systematic mixed studies review with qualitative synthesis A specialized health librarian searched MEDLINE, CINAHL, Embase Classic + Embase, PsycINFO, the Cochrane Library, Social Work Abstracts and Business Source Complete, together with grey literature data bases were searched from inception to November 29, 2012. This search was updated using forward citation tracking up to June 2014. Reporting quality was appraised and unclear articles were excluded. Included studies clearly reported OPR where the main research related decisions were co-constructed among the academic and healthcare organization partners. Included studies were distilled into summaries of their OPR processes and outcomes, which were subsequently analysed using deductive and inductive thematic analysis. All summaries were analysed; that is, data analysis continued beyond saturation. Results Eighty-three studies were included from the 8873 records retrieved. Eight key OPR processes were identified. Four follow the phases of research: 1) form a work group and hold meetings, 2) collectively determine research objectives, 3) collectively analyse data, and 4) collectively interpret results and decide how to use them. Four are present throughout OPR: 1) communication, 2) relationships; 3) commitment; 4) collective reflection. These processes contribute to extra benefits at the individual and organizational levels. Four ideal-types of OPR were defined. Basic OPR consists of OPR processes leading to achieving the study objectives. This ideal-type and may be combined with any of the following three ideal-types: OPR resulting in random additional benefits for the individuals or organization involved, OPR spreading to other sectors of the organization and beyond, or OPR leading to subsequent initiatives. These results are illustrated with a novel conceptual model. Conclusion The model provides operational guidance to help OPR stakeholders collaboratively address organizational issues and achieve desired outcomes and more. Review registration As per PROSPERO inclusion criteria, this review is not registered.